ECONOMIC ANALYSIS TO DETERMINE THE OPTIMUM AGE OF MARKETING LOCAL RED FEMALE TURKEY COCKS IN NENAVAH - Abdul Salam Mohammed Hussien (Mesopotamia Journal of Agriculture)
This study was made depending on field experiment data done at the college of Agriculture and Forestry/ University of Mosul. The experiment was concerned with breeding local red turkey cocks where three types of different compositions fodders, were given to these birds. Through statistical and economic analysis it was shown that the optimum age of marketing and selling local red turkey cock is the 17th week where the weight of each bird 2.193 kg. At this weight the net profit is (1807,700) dinar which is the greatest profit that could be attain under the current price and the fodder cost.